Training for Processing Plastic Waste into Oil Fuel - Mujiarto Mujiarto; Acep Wagiman; Ahmad Faisal bin Mohamad Ayob; Faisal Abdul Azis (Research Collaboration Community (RCC), 2022)
This service aims to provide education to elements of the community in Padamulya Village, Cihaurbeti District, Ciamis Regency. Next, we introduce to the public about plastic waste that can be used as fuel oil. The target of this activity is the community of one Padamulya, Cihaurbeti District, Ciamis Regency. This activity was attended by all regional leaders and the community. The expected result is that plastic waste produced by households can be used as fuel oil and reduce plastic waste in Padamulya village. Furthermore, training activities are carried out regularly so as to make the village healthy and economically independent.